GREEN MARKETING IN COFFEE SHOP : THE IMPACT ON CUSTOMER LOYALTY - Febriansyah, Ardilla Rahmanda (JURNAL ILMIAH EDUNOMIKA, 2024)
This research was conducted with the aim of analyzing the influence of green marketing on customer loyalty, the influence of brand authenticity on customer loyalty, the influence of green marketing on brand image, the influence of brand authenticity on brand image, the influence of brand image on customer loyalty. The research method uses quantitative methods. The type of research carried out is survey research. The researcher used a sample of 140 respondents. The analysis method in this research uses the Structural Equation Model (SEM) with the SmartPLS analysis tool. According to the explanation above, researchers are interested in conducting research with the title "Green Marketing in Coffee Shop: The Impact on Customer Loyalty". Keywords: Green, pengaruh, Customer Loyalty, Brand Authenticity, Brand Image